Ground Motion Parameters and Resonance Effect During Strong Earthquake in Northern Thailand - Mase, Lindung Zalbuin; Likitlersuang, Suched; Tobita, Tetsuo (Geotechnical and geological engineering, 2021)
Several previous investigations have suggested that ground motion as described by various parameters and resonance effects could have contributed to the damage observed during an earthquake. This paper presents a ground motion parameters study and site investigation in Northern Thailand during the Tarlay Earthquake of 2011. Ground motion parameters recorded at the closest seismic station to the earthquake rupture, i.e. Mae Sai Station (MSAA) are studied. Microtremor measurement was performed at the MSAA site. The horizontal to vertical spectral ratio (H/V) from the investigation are interpreted. Spectral acceleration ratios based on data from the MSAA are compared to determine the possibility of resonance during the earthquake. Spectral acceleration data based on recorded ground motion are compared to guideline design spectral acceleration to determine the critical period. Results show that during the Tarlay Earthquake, significant duration was 24 s. Within this duration, resonance was plausible within the frequency range of 1.82 to 2.1 The critical period ranged from 0.4 to 0.6 s, indicating that low-medium story buildings were most vulnerable. Results also show that horizontal ground motion was relatively dominant in the destruction of structural buildings during the earthquake.